Migration of interneuron precursors in the nascent cerebellar cortex - Wefers, Annika K. (The cerebellum, 2018)
The cerebellum arguably constitutes one of the best characterized central nervous circuits, and its structure, cellular function, and histogenesis have been described in exceptional quantitative detail. A notable exception to this is the development of its inhibitory interneurons, and in particular the extensive migrations of future basket and stellate cells. Here, we used acute slices from 8-day-old mice to assess the migration of Pax2-EGFP-tagged precursors of these cells en route to the molecular layer during their transit through the nascent cerebellar cortex. We document that movement of these cells is highly directed. Their speed and directional persistence are larger in the nascent granule cell layer than in the molecular layer. And they migrate periodically, with periods of effective, directed translocation separated by bouts of rather local movement. Finally, we document that the arrangement of these cells in the adult molecular layer is characterized by clustering. These data are discussed with a focus on potential generative mechanisms for the developmental pattern observed.